Evaluating the Effectiveness of Intranasal Estrogen on Nasal Obstruction in Menopausal Women: A Randomized Clinical Trial Study - Behrouz Barati; Ali Goljanian Tabrizi; Mahboobe Asadi; Khadijeh Moghadam (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum)
Background and Objectives: Nasal obstruction is a common complaint in menopausal women. This study was conducted with the aim of investigating the effectiveness of intranasal estrogen on nasal obstruction in menopausal women. Methods: This study is a three-blind, placebo-controlled randomized clinical trial that was conducted on menopausal women with nasal obstruction in Taleghani Hospital, Tehran in 1400. The patients were selected as available and randomly divided into intervention and control groups. The intervention group was treated with intranasal estrogen ointment and the control group was treated with intranasal lanolin (placebo) daily for three months. The data were analyzed using t-test with SPSS software, version 21. Results: 46 menopausal patients with nasal obstruction,an average age of 52.58±0.667 years, and an average body mass index of 23.33±3.42 kg/m2 were included in the study.then, the patients were randomly divided into two groups,an intervention group (23 people) and the control group (23 people). No significant difference was observed in the demographic data between the groups. All patients showed a significant improvement in the severity of symptoms and rhinomanometry results after three months. In post-intervention visits , the mean severity of nasal obstruction and rhinomanometry results in the intranasal estrogen group were significantly higher than the placebo group.(P<0.05) Conclusion: According to the results of the study, it is suggested to use intranasal estrogen ointment to treat nasal obstruction in menopausal women with out anatomical or functional nasal disorders.